Using Epoxy Resin as a Bitumen Additive to Solve Cracking in Flexible Pavements - Calvin Ngobi (Uganda Christian University, 2025)
This report presents research and findings carried out in the modification of bitumen using epoxy resin as a bitumen extender to curb oxidation in bitumen that results in bitumen aging which later results into it cracking and indicates how the epoxy resin bitumen extender will behave when applied in bitumen for roads in the tropical region for example Uganda. A case study of Rwentobo-Katuna flexible pavement which developed cracks in the first year of its defect’s liability period due to oxidative cracking which exists in the south-western Uganda is taken. This report presents findings of the trials of improvement of bitumen, with 2%,3% and 5% epoxy resin, a 3% optimum improved bitumen’s resistance to oxidative ageing with a percentage reduction of % mass loss from the RTFOT of 38.46% which shows a better improvement in resistance to oxidative aging among other improved properties that are represented in later chapters.
UNDERGRADUATE